Comparative of mediator approach for database integration - Mohd Kamir, Yusof; Md Yazid, Mohd Saman; Wan Nor Shuhadah, Wan Nik (2015)
Six applications which are based on mediator approach have been reviewed in this study. In practice, The mediator is used to integrate and access data from different data sources. The important characteristics for the implementation of mediator approach have been identified. This include types of data, file format and object data. These characteristics together with the advantages and the disadvantages of each implementation mediator approach described in section 4. This is important for other researchers to do the literature review. Indeed, this study highlights important issues that need to be addressed before future directions for the research in the area of database integration based on mediator is channelled.